The Role of Administrative Transparency in Strengthening Psychological Contract Commitment «An Applied Study» - Al-Gharably, Zeinab; Al-Banna, Hatem (The Arab Journal of Administration, 2022)
The researchers seek through to determine the level of administrative transparency, and determine the level of commitment to the psychological contract, and determine the type and strength of the relationship between administrative transparency in its various dimensions and the level of commitment to the psychological contract The results showed that the reality of applying administrative transparency was medium and high at the overall level and for each dimension separately, and there are statistically significant differences between the perceptions of workers towards the reality of administrative transparency taken overall, and towards each of its variables. The study also found that the psychological contract commitment was average and high at the overall level and for each dimension, and the absence of statistically significant differences between the perceptions of workers towards the level of commitment to the psychological contract taken in total, and the existence of statistically significant differences between the perception of workers in the local units of Kafr Al-Sheikh governorate. And about each variable of the level of commitment to the psychological contract individually, depending on the type, age and scientific qualification, and the existence of a strong positive correlation with statistical significance between the dimensions of administrative transparency combined and the dimensions of commitment to the psychological contract combined, and the researchers reached a set of recommendations on how to improve the psychological contract commitment of the workers in the local units in Kafr Sheikh governorate through administrative attention to transparency.